FAKTOR-FAKTOR PENYEBAB TERJADINYA KEPEMILIKAN TANAH ABSENTEE DI KECAMATAN TONDANO SELATAN KABUPATEN MINAHASA - Jeine Leyliana Robot; Caroline Betsi Diana Pakasi; Noortje Marselianie Benu (AGRI-SOSIOEKONOMI, 2020)
The research aims to analyze the factors causing the absentee / guntai ownership of agricultural land and to analyze the decision making by the Land Office of Minahasa District in terms of absentee / guntai ownership of agricultural land in Tondano District, Minahasa Regency. The research location is located in Tondano Selatan Sub-district, Minahasa Regency, and Land Office of Minahasa Regency. The research period lasted for five months, namely, January to June 2020. The data used consisted of primary data and secondary data. Primary data obtained through in-depth interviews (In-depth Interview). Secondary data were obtained from available data from other sources such as documents related to the discussion, literature, and documentation that were in accordance with the research objectives. The samples in this study were chosen deliberately. The sample of this research includes 2 kinds of samples, namely, the key sample and the main sample. This study used a qualitative data analysis method. The results showed that the determinant factors causing absentee land ownership are: knowledge factors, awareness factors, cultural factors, law enforcement factors, and economic value factors. Meanwhile, decision-making in enforcing the rules regarding the absentee prohibition of land ownership in Tondano Selatan District, Minahasa Regency has not been implemented optimally.*eprm*